Enhancing The Efficiency of The School Library as a Learning Resource - Ramadhan, All Rizky; Ayasi, Amar (International Journal of Cultural and Social Science, 2024)
This article seeks to examine the utilization of school libraries as a primary resource for acquiring educational information within educational institutions. The research employed a qualitative methodology with a descriptive approach. The informant selection technique employs purposive sampling. There were a total of 5 informants, all of whom were teachers specifically assigned to oversee the library. The research findings demonstrate that school libraries are extensively utilized by both students and teachers as a valuable resource for acquiring educational information. The library collections are utilized as a reference for student assignments at school, ensuring their effective utilization. In addition, the coordination between teachers and the library operates efficiently, evident in the collaboration between subject teachers and the library in formulating lesson plans.